Rekonstruksi Kepemimpinan Kristen sebagai Otoritas Epistemik di Era Disinformasi Digital: Model Literasi Moderasi Beragama bagi Generasi Z - Herbin - Simanjuntak; Talizaro Tafonao; Johannes - Ndruru; Radius - Simanjuntak (Sekolah Tinggi Teologi Nusantara, 2026)
The flow of religious disinformation in digital spaces not only shapes religiosity among Generation Z but also exposes the limitations of Christian leadership paradigms that have traditionally operated within institutional, hierarchical, and pulpit-centered frameworks. This condition has led to a crisis of authority, weak critical literacy among Christian leaders, and the absence of operational strategies for religious moderation in digital environments. This study aims to critically analyze the limitations of prevailing Christian leadership paradigms in addressing religious disinformation while simultaneously reconstructing a leadership framework that is relevant to Generation Z. Employing a qualitative approach through a critical literature review, this study conducts a conceptual analysis of theories of Christian leadership, digital literacy, and religious moderation. The findings indicate that the challenges posed by the era of disinformation cannot be addressed through technological adaptation alone; rather, they require a paradigm reconstruction that positions critical literacy, ethical exemplarity, and interfaith collaboration as core leadership competencies. This study contributes to the development of a contextualized theoretical framework for Christian leadership and offers practical implications for strengthening the digital resilience of Generation Z.Abstrak:Arus disinformasi keagamaan di ruang digital tidak hanya berdampak pada pola keberagamaan Generasi Z, tetapi juga mengungkap keterbatasan paradigma kepemimpinan Kristen yang selama ini beroperasi dalam kerangka institusional, hierarkis, dan mimbar-sentris. Kondisi ini memunculkan krisis otoritas, lemahnya literasi kritis pemimpin Kristen, serta absennya strategi moderasi beragama yang operasional di ruang digital. Penelitian ini bertujuan menganalisis secara kritis keterbatasan paradigma kepemimpinan Kristen dalam menghadapi disinformasi keagamaan, sekaligus merekonstruksi kerangka kepemimpinan yang relevan bagi Generasi Z. Penelitian ini menggunakan pendekatan kualitatif melalui kajian pustaka kritis dengan analisis konseptual terhadap teori kepemimpinan Kristen, literasi digital, dan moderasi beragama. Hasil kajian menunjukkan bahwa tantangan era disinformasi tidak dapat dijawab melalui adaptasi teknologis semata, melainkan memerlukan rekonstruksi paradigma kepemimpinan yang menempatkan literasi kritis, keteladanan etis, dan kolaborasi lintas iman sebagai kompetensi inti. Penelitian ini berkontribusi pada pengembangan kerangka teoretis kepemimpinan Kristen yang kontekstual serta menawarkan implikasi praktis bagi penguatan ketahanan digital Generasi Z. Kata Kunci: Kepemimpinan Kristen; Generasi Z, Literasi, Moderasi Beragama.